The entanglement between traditions and colonial spatiality: The resilience of Guinean domesticities in the Ajuda neighborhood, Bissau - Vita, F. (Traditional Dwellings and Settlements Review, 2023)
Local traditions have always been endangered by colonialism and modernity. For centuries under Western systems of domination in Africa they were exploited for colonial purposes and even subverted, and in many cases they were reinvented under both modern and imperial discourses. Nevertheless, new traditions have also emerged from both colonial and modern legacies that today shape contemporary social and spatial landscapes. To explore these issues, this article examines the Ajuda neighborhood in Guinea-Bissau’s capital of Bissau, which was built in the 1960s under Portuguese colonial rule to accommodate mainly public servants and their families from the African population. It aims to unveil how Guinean traditions related to dwelling space, reorganized within the colonial spatiality, have reemerged to shape and transform present-day domestic environments. Using the house as a critical tool, the article discusses how traditions may thus endure as long as they are negotiated in relation to new conditions that may derive from disruptive events, such as colonialism.